EFFECTIVITY ANTIBACTERIAL ZINC OXIDE EUGENOL WITH ZINC OXIDE PROPOLIS FOR ENDODONTIC TREATMENT IN PRIMARY TEETH - Erwid Fatchur Rahman; Sandy Christiono (ODONTO : Dental Journal, 2019)
Background: Enterococcus faecalis is generally found on the failure of root canal treatments. Zinc oxide propolis is believed to have an antibacterial effect on that bacteria. This research aimed to compare bacteriostatic effect of zinc oxide eugenol (ZOE) and zinc oxide propolis (ZOP) as the sealer materials of root canal.Method: This was an experimental research with post-test only control group design with two different groups (ZOE and ZOP). Culture of Enterococcus faecalis bacteria was smeared on Blood Agar Plate media with six times replication per group and kept inside incubator for 24 hours. The result was obtained from the inhibition zone formed around the pasta.Result: The average result of ZOE and ZOP was 27.7 mm and 13.45 mm respectively. Normality test using Shapiro-Wilks showed that data was normal (p>0.05). Then, the data was analysed using Independent Samples T-test. The result showed that there was different inhibition zone between ZOE group and ZOP group (p<0.05).Conclusion: Based on the result, it can be concluded that ZOP has lower antibacterial effectiveness of the Enterococcus faecalis than ZOE.